A post-traumatic stress disorder among internally displaced people in sub-Saharan Africa: a systematic review - Koshe, Tura; Jarso, Mohammedamin Hajure; Walde, Mandaras Tariku; Ebrahim, Jemal; Mamo, Aman; Esmael, Adem; Wedajo, Lema Fikadu; Seife, Solomon; Mohammedhussein, Mustefa; Nigatu, Desalegn; Debele, Gebiso Roba; Gezmu, Wubishet (Frontiers in Psychiatry, 2023)
Introduction Despite the prevalence of post-traumatic disorder in internally displaced persons, which is well established, and the fact that respective international organizations are working on the issues, little attention is given in the context of sub-Saharan Africa, This study aims to review the available data about the prevalence and determinants of post-traumatic stress disorders among internally displaced people in sub-Saharan Africa. Methods Studies published in the English language that have a clear outcome of interest and are available in full text were included. Six electronic databases were searched to identify published studies on the prevalence and determinants of posttraumatic stress disorder among IDPs in sub-Saharan Africa. This includes PubMed/MEDLINE, Scopus, EMBASE, PsychInfo, and the Web of Science. All relevant studies till June, 2023 were assessed. The review was done as per the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA-2009) and registered on PROSPERO (CRD420222997111). Results Originally, 33,138 articles were found in six databases, and finally, eleven studies were reviewed. The prevalence of post-traumatic stress disorder in sub-Saharan African countries was disproportionately presented in this review, ranging from 12.3% in Central Sudan to 85.5% in Nigeria. From a total of 11 studies, eight of them reported more than 50% of the magnitude of post-traumatic stress disorder, pointing to a higher magnitude of the prevalence of post-traumatic stress disorders in the region. The study identified numerous factors that contributed to post-traumatic stress disorder among the internally displaced population. Female gender, depression, anxiety, stress, being single, low level of educational status, experiencing or witnessing traumatic events, and psychological trauma were evidenced for their association with post-traumatic stress disorder. Conclusion These results demonstrate a higher prevalence of post-traumatic stress disorder compared to other regions of the world. The participants’ socio-demographic characteristics, including age, being single, being female, and a low level of education, were identified as factors contributing to PTSD. Moreover, the review identified that depression, anxiety, and experiencing or witnessing traumatic events were also influencing factors for PTSD among IDPs. The concerned bodies need to reinforce the monitoring and evaluation of the mental health programs of IDPs in the region. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=299711, CRD42022299711.